Overpromising and underperforming? : understanding and evaluating new intergovernmental accountability regimes - Graefe, Peter; Simmons, Julie M., 1974-; White, Linda A. (Linda Ann), 1967- (Institute of Public Administration of Canada series in public management and governance., 2013)
"Public reporting has been used experimentally in federal-provincial relations since the mid-1990s as an accountability mechanism to promote policy effectiveness, intergovernmental cooperation, and democratic legitimacy. Our understanding of how well it is working, however, remains limited to very specific policy sectors - even though this information is essential to policy makers in Canada and beyond. Overpromising and Underperforming? offers a deeper analysis of the use of new accountability mechanisms, paying particular attention to areas in which federal spending power is used